Hit & Run : Interventions, Performances throughout Istanbul. - Peutz, Thomas; Henry, Una (Amsterdam : SMART Project Space, 2004)
Bijl, Marc ; Artigas, Gustavo ; Shipsides, Dan ; Bain, Marc ; Drôge Wendel, Yvonne ; Framis, Alicia ; Audéoud, Fabienne ; Warner, Deborah ; Allen, Dave ; Beckett, James ; Tatham, Joanne & O'Sullivan, Tom ; Pérez, Asier ; Muñoz, Begoña
Istanbul, July 2004. SMART project Space in collaboration with Platform Garanti Contemporary Art Center, Istanbul, 23 June - 28 July 2004
boek